2016
DOI: 10.1002/ange.201600275
|View full text |Cite
|
Sign up to set email alerts
|

Stability of B12(CN)122−: Implications for Lithium and Magnesium Ion Batteries

Abstract: Multiply charged negative ions are seldom stable in the gas phase. Electrostatic repulsion leads either to autodetachment of electrons or fragmentation of the parent ion. With a binding energy of the second electron at 0.9 eV, B12H122− is a classic example of a stable dianion. It is shown here that ligand substitution can lead to unusually stable multiply charged anions. For example, dodecacyanododecaborate, B12(CN)122−, created by substituting H by CN is found to be highly stable with the second electron boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
88
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 29 publications
4
88
0
Order By: Relevance
“…When one of the B atoms in the B 12 (CN) 12 is replaced by C, ΔE 1 of CB 11 (CN) 12 is 8.72 eV which is also much larger than that of CB 11 H 12 . More importantly, the second electron in CB 11 (CN) 12 2− is bound by 1.07 eV, while the CB 11 H 12 2− dianion is unstable compared to its monoanion state. It was further found that the binding energies of Mg 2+ and Li + to CB 11 (CN) 12 2− and CB 11 (CN) 12 − , respectively, are also significantly lower than those bound to CB 11 H 12 2− and CB 11 H 12 − .…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…When one of the B atoms in the B 12 (CN) 12 is replaced by C, ΔE 1 of CB 11 (CN) 12 is 8.72 eV which is also much larger than that of CB 11 H 12 . More importantly, the second electron in CB 11 (CN) 12 2− is bound by 1.07 eV, while the CB 11 H 12 2− dianion is unstable compared to its monoanion state. It was further found that the binding energies of Mg 2+ and Li + to CB 11 (CN) 12 2− and CB 11 (CN) 12 − , respectively, are also significantly lower than those bound to CB 11 H 12 2− and CB 11 H 12 − .…”
Section: Introductionmentioning
confidence: 92%
“…It was further found that the binding energies of Mg 2+ and Li + to CB 11 (CN) 12 2− and CB 11 (CN) 12 − , respectively, are also significantly lower than those bound to CB 11 H 12 2− and CB 11 H 12 − . All these properties indicate that B 12 (CN) 12 2− and CB 11 (CN) 12 − might serve as the anionic components of electrolytes inside metal-ion-based batteries. However, the cyanide ion CN − is highly toxic which will make it difficult to synthesize B 12 (CN) 12 2− in experiment.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations